The Application of School-Based Management in Developing Teacher Professionalism - Faujiah Ramud; Amiruddin Siahaan; Salminawati (JTP - Jurnal Teknologi Pendidikan, 2026)
This study aims to conduct an in-depth analysis of the implementation of School-Based Management (SBM) in developing teacher professionalism at State Senior High School 1 Medan and State Model Senior High School 2 Medan. This study employs a qualitative approach with a multisite design, where data collection was conducted through in-depth interviews, participatory observation, and document analysis, involving school principals, vice principals, teachers, school committees, and school supervisors. The results indicate that the implementation of MBS at both schools has significantly contributed to enhancing teacher professionalism, though with distinct implementation characteristics. At MAN 1 Medan, MBS was implemented with an emphasis on program implementation, work discipline, and compliance with learning administration standards. Planning and evaluation were conducted periodically, but tended to remain administrative in nature, short-term in orientation, and not yet fully integrated with teachers’ continuous professional development. In contrast, MAN 2 Model Medan demonstrates a more systematic, participatory, and quality-culture-based implementation of MBS. Program planning is based on needs analysis and teacher performance data; implementation is focused on strengthening the professional learning community; and evaluation is utilized as an organizational learning tool that fosters collective reflection and innovation in teaching practices. This study offers new findings that the effectiveness of MBS in the madrasah context is determined not only by school management autonomy but also by the internalization of Islamic values and the development of a reflective culture among teachers as part of the madrasah’s internal quality assurance system.